PENGARUH PENDUDUK, PENGHASILAN DAN PAJAK TERHADAP PERMINTAAN PERUMAHAN JAWA TENGAH TAHUN 2019 - Sari, Ratna Tunjung (Jurnal Riptek, 2020)
One of the compulsory needs of Indonesian citizens is the fulfillment of the needs of boards (houses) which are increasing in number every day, so the government is required to determine the right policy strategy in its control so that it can remain in line with other sectors. This study takes the object of 26 districts and cities in Central Java, by looking at the situation and environmental conditions that are increasingly dense with all economic activity and growth. This study uses a quantitative method with secondary data collection using BPS, the Tax Office and the Government of Central Java Province in 2013-2018 and tested using panel data regression. In the study concluded that there is a positive and significant effect between the population (X1) and housing demand, there is a positive but not significant effect of population income (X2) on housing demand and there is a negating and significant effect between tax (X3) on housing demand (Y) and together - the total population, per capita income and tax have an effect of 93.5% on the demand for housing in Central Java in 2019.